Microbiological control of moisturizing mask formulation added of hibiscus flowers, assai palm, black mulberry and papaw glycolic extracts - Oliveira, Marcela B. [UNESP]; Vieira, Daniela C. M. [UNESP]; Fiúza, Thalita M. [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chorilli, Marlus [UNESP] (My University, 2013)
The microbiological control of moisturizing mask formulation added of hibiscus flowers, assai palm, black mulberry and papaw glycolic extracts, determining the number of viable microorganisms and possible presence of pathogenic. The moisturizing mask formulation was composed of zinc oxide (5. 0%) and moisturizing cream constituted of triceteareth-4 phosphate (and) cetyl alcohol (and) stearyl alcohol (and) sodium cetearyl sulfate (and) oleth-10 (qs 50g). To this formulation was added hibiscus flowers glycolic extract (2. 5%), assai palm glycolic extract (1. 5%), black mulberry glycolic extract (1. 5%) and papaw glycolic extract (2. 0%). The formulation was stored in aseptically clean recipients, away from humidity and light, in fresh and airy places. The results of the microbiological analysis on the counting of aerobic mesophilic microorganisms (bacteria and fungi), of the above mentioned formulation, revealed a bioburden < 10 CFU/mL in all samples. Such data indicate adequate microbiological quality of the tested products, according to official recommendations. Furthermore, it was not detected the presence of pathogenic microorganisms, assuring the harmlessness of the formulation. The results lead us to conclude that the formulation and raw materials analyzed did not present microbial contamination, evidenced for estimating the number of viable microorganisms (<10 UFC/g) and for researching pathogens.
Keywords: Glycolic extracts. aerobic mesophile microorganisms; Microbiological control; Moisturizing mask formulation; assai palm extract; black mulberry extract; hexadecanol; hibiscus flower extract; octadecanol; papaw extract; plant extract; unclassified drug; zinc oxide; clonogenic assay; controlled study; drug delivery system; drug formulation; Escherichia coli; humidity; light; microbial contamination; microbial growth; microbiological parameters; microorganism; moisturizing mask formulation; nonhuman; pathogenesis; Pseudomonas aeruginosa; quality control; Salmonella; Staphylococcus aureus